In vitro algicidal effect of guanidine on Prototheca zopfii genotype 2 strains isolated from clinical and subclinical bovine mastitis. (1st June 2017) - Alves, A.C.; Capra, E.; Morandi, S.; Cremonesi, P.; Pantoja, J.C.F.; Langoni, H.; de Vargas, A.P.C.; da Costa, M.M.; Jagielski, T.; Bolaños, C.A.D.; Guerra, S.T.; Ribeiro, M.G.
Abstract: Prototheca species have increasingly been reported to be opportunistic pathogens that cause mastitis in dairy herds, and it poses an emergent problem because at present, there are no effective therapies for the treatment of protothecal mastitis. This study investigated the in vitro algicidal effect of guanidine on 75 Prototheca zopfii genotype 2 strains isolated from 75 cases of clinical and subclinical bovine mastitis. All strains were susceptible to guanidine in vitro with minimal algaecide concentrations ranging from 0·001 to 0·035%. Guanidine is known to have a high microbicidal effect and is considered to be a new generation microbicidal compound. It is not toxic to human mucous membranes and conjunctivas at low concentrations and has been used as a disinfectant in swimming pools and as an antiseptic for human wounds. The algicidal action of guanidine at low concentrations indicates that it could be an alternative disinfectant or antiseptic for cleaning of the dairy environment and milking equipment, in pre‐ and postdipping solutions, in the chemical dry therapy of bovine teats and even in the intramammary therapy of P. zopfii infections. This is the first report of the in vitro algicidal effect of guanidine on P. zopfii strains of animal origin. Significance and Impact of the Study: Prototheca zopfii genotype 2 is an opportunistic pathogen of bovine mastitis. To date, no effective therapies against protothecal mastitis have been developed. The in vitro algicidal effect of guanidine on 75 P. zopfii genotype 2 strains isolated from cows revealed that all of the isolates were susceptible to the compound at low concentrations, which indicates that guanidine may be used as an antiseptic/disinfectant for dairy milking equipment, in pre‐ and postdipping solutions, and as a chemical dry therapy or an intramammary therapy. This study describes the in vitro algicidal effect of guanidine on P. zopfii for the first time.